Savoring satiety: an exploratory analysis of the neural correlates of sensory-specific satiety - Simon, Joe J.; Müller, Tim; Schöner, Fabian; Bendszus, Martin; Friederich, Hans-Christoph (Nutrients, 2025)
Background/Objectives: Sensory-specific satiety (SSS) refers to the decrease in pleasantness of a food after repeated consumption, while other foods remain appealing. Despite its significance in hedonic food perception, the underlying mechanisms of SSS remain poorly understood. This study aimed to investigate the neurobiological basis of SSS and its relationship with body weight and hedonic food perception. Methods: Twenty-three healthy individuals with varying body weights underwent functional magnetic resonance imaging during a novel gustatory stimulation procedure. SSS was induced by repeated exposure to glucose, during which the hedonic perception of a neutral stimulus increased. Results: We found that SSS was associated with a network of brain regions related to reward and taste processing, including the lateral orbitofrontal cortex. Increased activation in the medial prefrontal cortex was related to both the expectation and receipt of a neutral stimulus with increased hedonic value during SSS. Finally, higher body weight was related to decreased activation in the medial prefrontal cortex, whereas an increased tendency for food craving was associated with increased activation of the lateral orbitofrontal cortex during SSS. Conclusions: Our results extend previous findings of an orbitofrontal-cortex-mediated shift in hedonic perception of food during SSS and show that the medial prefrontal cortex plays a crucial role in reward value modulation during SSS. Furthermore, our results indicate that increased BMI and trait food craving are associated with altered reward processing during SSS. Taken together, our results provide new insights into the neural mechanisms underlying changes in hedonic food perception during SSS.
Veröffentlicht: 15. Oktober 2025
Gesehen am 02.12.2025